Negative Ultraselection of Patients With RAS/BRAF Wild-Type, Microsatellite-Stable Metastatic Colorectal Cancer Receiving Anti–EGFR-Based Therapy. (11th May 2022) - Randon, Giovanni; Maddalena, Giulia; Germani, Marco Maria; Pircher, Chiara Carlotta; Manca, Paolo; Bergamo, Francesca; Giordano, Mirella; Sposetti, Caterina; Montagna, Aldo; Vetere, Guglielmo; Zambelli, Luca; Rasola, Cosimo; et al.
Abstract : PURPOSE: Several uncommon genomic alterations beyond RAS and BRAFV600E mutations drive primary resistance to anti–epidermal growth factor receptors (EGFRs) in metastatic colorectal cancer (mCRC). Our PRESSING panel (including PIK3CA exon 20/ AKT1 / PTEN mutations, ERBB2 / MET amplifications, gene fusions, and microsatellite instability-high status) represented a paradigm of negative hyperselection with more precise tailoring of EGFR blockade. However, a modest proportion of hyperselected mCRC has intrinsic resistance potentially driven by even rarer genomic alterations. MATERIALS AND METHODS: A prospective data set at three Italian Academic Hospitals included 650 patients with mCRC with comprehensive genomic profiling by FoundationOne CDx and treated with anti-EGFRs. PRESSING2 panel alterations were selected on the basis of previous clinico-biologic studies and included NTRKs, ERBB3, NF1, MAP2K1 / 2 / 4, AKT2 pathogenic mutations; PTEN / NF1 loss; ERBB3, FGFR2, IGF1R, KRAS, ARAF, and AKT1-2 amplification; and EGFR rearrangements. These were collectively associated with outcomes in patients with hyperselected disease, ie, RAS / BRAF wild-type, PRESSING-negative, and microsatellite stable. RESULTS: Among 162 hyperselected patients, 24 (15%) had PRESSING2 alterations, which were mutually exclusive except in two samples and were numerically higher in right-sided versus left-sided cancers (28% v 13%; P = .149). Independently of sidedness and other factors, patients with PRESSING2-positive status had significantly worse progression-free survival and overall survival compared with PRESSING2-negative ones (median progression-free survival 6.4 v 12.8 months, adjusted hazard ratio 4.19 [95% CI, 2.58 to 6.79]; median overall survival: 22.6 v 49.9 months, adjusted hazard ratio 2.98 [95% CI, 1.49 to 5.96]). The combined analysis of primary tumor sidedness and PRESSING2 status allowed us to better stratify outcomes. CONCLUSION: Negative ultraselection warrants further investigation with the aim of maximizing the benefit of EGFR blockade strategies in patients with RAS and BRAF wild-type, microsatellite stable mCRC. Abstract : Beyond RAS/BRAF: rarer alterations drive negative ultraselection for anti-EGFR therapy in mCRC